Energy dissipation and slalom turn radius - Gilgien, M.; Reid, R.; Tjørhom, H.; Moger, T.; Haugen, P.; Kipp, R.; Smith, G. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Earlier studies (Supej et al., 2005) have compared energy dissipation (EDISS) with ski turn radius. There is reason to believe, however, that EDISS will follow the center of mass turn radius (RCOM) more closely. The aim of this study is to compare the relationships between the turn radius of the outer ski (RSKI), RCOM. and EDISS.